Simultaneous Determination of Lactulose and Lactose in Conserved Milk by HPLC-RID - Michelle Fernandes Silveira; Lourdes Maria Pessôa Masson; José Francisco Pereira Martins; Thiago da Silveira Álvares; Vânia Margaret Flosi Paschoalin; César Lázaro de la Torre; Carlos Adam Conte-Junior (Journal of Chemistry)
Heat treatment is applied to dairy products to ensure microbiological quality and increase the shelf life. However, a suitable control of this process is necessary to guarantee nutritional and sensory quality. The aim of this study is to adapt the high performance liquid chromatography (HPLC) method for determination of lactulose and lactose content in commercial samples of UHT and sweetened condensed milk. The HPLC method used showed a good resolution of the analytes evaluated. The analyzed UHT milk samples presented levels for lactulose in accordance with the limit recommended by the International Dairy Federation. There was no significant variation in lactulose concentration for sweetened condensed milk samples. However, one sweetened condensed milk sample showed lactose level lower than the established values (10–12%).